Perluasan Target Pasar UMKM Barongan dan Pengenalan Kerajinan Barong Khas Blitar Melalui Digital Marketing - Yeyen Andriana; Niniek Imaningsih; Cholid Fadil (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
The problem with the current target market for traditional handicrafts is that the younger generation in Indonesia, both in cities and in regions, are less interested in the surrounding culture, besides that the limited ability of craftsmen to take advantage of technological developments is also an obstacle in expanding the target market. So that this service is carried out with the aim of solving various problems faced by the UMKM Wisanggeni Art Gallery in expanding the market and introducing culture to the wider community. Preserving culture is also included in efforts to defend the country which may rarely be considered. Each region has various types of Barong, one of which is the typical Blitar City Barongan. The characteristics of the typical Blitar Barogan can be seen from the shape, color, and motifs which describe a personality that is firm and fierce but likes to joke or play and is often nicknamed "Ngucing". The raw material for making Barongan is large and heavy wood. The method for carrying out community service activities is divided into three stages, namely introduction, implementation, and evaluation. The purpose of this service is to expand the target market for Barongan UMKM through the implementation of a digital marketing system by creating an online shopping platform in the form of a Shopee sales application and several social media accounts such as Instagram and Tiktok as a medium for expanding product information, besides that the author also provides education about creating content that attracts buyers.